(untitled) (Vallis Aurea, 2018)
In recent years, external trade figures between Croatian and Hungarian have marked significant changes. Although, both of them have been passed strong process of transformation in the earlier nineties of the last century. In the observed period, Hungarian export marked significant result in terms of external coverage ratio and it is continuously in the surplus side. Comparing with Croatia, the results are totally different; low external trade coverage ratio (in average below 60%) and continuously in the deficit side. Therefore, the main goal of this article is to point out how depreciation of exchange rate in correlation with internal depreciation influence on the net foreign direct investment inflow (hereinafter FDI) and external trade balance. Thus, in the observed period Hungary had significant high level of capital accumulation in terms of FDI, followed with high level of internal depreciation and depreciation of exchange rate, while Croatian economy, had considerably lower level of capital accumulation measured in terms per capita FDI followed with internal appreciation and stable exchange rate. Additionally, in the observed period, Croatia had passed through the recession which lasted six years, while in Hungary that was not the case.